Clinical characteristics and predictive factors of recurrent idiopathic transverse myelitis - Lee, Eun Kyoung; Kim, Sooyoung; Sohn, Eunhee (Frontiers in Neurology, 2024)
Background Idiopathic transverse myelitis (iTM) is defined as an inflammatory myelopathy of undetermined etiology, even after a comprehensive workup to identify other possible causes. Generally, the characteristics of recurrent iTM are not clearly defined. This study aimed to identify the clinical characteristics and predictive factors of recurrence in patients with iTM. Methods We retrospectively recruited patients with transverse myelitis (TM) who visited Chungnam National University Hospital between January 2011 and December 2021. We included patients who were followed up for at least 2 years and excluded those diagnosed with multiple sclerosis or neuromyelitis optica spectrum disorder (NMOSD) during the initial episode or follow-up period. Patients with iTM were categorized into two groups: monophasic idiopathic TM (mTM) and recurrent idiopathic TM (rTM). We compared the clinical characteristics and spinal magnetic resonance imaging findings between the two groups. Results In total, 167 patients were reviewed, of whom 112 were excluded. Finally, we included 55 patients with iTM. In 55 patients, 11 (20.0%) and 44 (80%) were classified into the rTM and mTM groups, respectively. Male predominance was observed in the iTM, rTM, and mTM groups. The percentage of patients with low vitamin D levels was significantly higher in the rTM group (100.0%) compared with the mTM group (70%) (p = 0.049). In addition, longitudinally extensive transverse myelitis (LETM) was observed more frequently in the rTM group, in 8 of 11 (72.7%) patients, compared with 15 of 44 (34.1%) patients in the mTM group, with the difference being statistically significant (p = 0.020). In multivariate regression analysis, female sex, younger age at onset, low serum vitamin D level (<30 ng/mL), and LETM were risk factors for recurrence. LETM was a significant predictor of relapse in iTM (p = 0.043, odds ratio = 13.408). Conclusion In this study, the clinical features of mTM and rTM are nearly indistinguishable. In conclusion, >20% of the patients with iTM experience recurrence, and LETM is the most significant risk factor for recurrence. In cases of recurrence, there is a favorable response to immunotherapy, and the prognosis is generally good. Although LETM may be the initial symptom of NMOSD, it may be manifestation of iTM, and in cases of idiopathic LETM, it is important to be mindful of the elevated risk of recurrence. Based on these results, idiopathic rTM has good clinical prognosis and response to immunosuppressive treatment.